Surfactants and detergents : chemistry and applications - Rizvi, Syed Q. A., 1945- (ASTM's manual series, 2021)
"Two common terms used to describe surface-active materials are amphiphiles and surfactants. The term amphiphile is derived from Greek-amphis meaning "both" and philia meaning "love or friendship." An amphiphilic chemical is a chemical whose molecular structure has one or more hydrophilic groups and one or more hydrophobic groups. Another Greek-derived synonymic term used to describe amphiphilic chemicals is amphipathic (amphis meaning "both" and pátheia meaning "feeling"). Because all surfactants possess hydrophilic and hydrophobic groups, they are termed as amphiphilic or amphipathic compounds. The term surfactant, a contraction of surface-active agent, implies the material is active at surfaces. Surfactants have the tendency to adsorb at surfaces as well as interfaces. The difference between surfaces and interfaces is that surfaces involve a gas, usually air, as one of the phases, and the interfaces are boundaries between two immiscible phases. Five interfaces are possible from three common states of matter (solid, liquid, and gas)"--